First report on the molecular phylogenetics and population genetics of Aedes aegypti in Iran - Azim Paksa; Kourosh Azizi; Saideh Yousefi; Sorna Dabaghmanesh; Saeed Shahabi; Alireza Sanei-Dehkordi (Parasites & Vectors, 2024)
Abstract Background Aedes aegypti, the primary vector of various human arboviral diseases, is a significant public health threat. Aedes aegypti was detected in Iran in 2018, in Hormozgan province, but comprehensive information regarding its genetic diversity and origin within the country remains scarce. This study aimed to determine the origin and genetic diversity of Ae. aegypti in southern Iran. Methods Aedes aegypti mosquitoes were collected from Bandar Abbas City, Hormozgan Province, southern Iran, between May and July 2022. Specimens were morphologically identified. Origin and assess genetic diversity were assessed based on the mitochondrial DNA-encoded cytochrome c oxidase subunit I (mtDNA-COI) gene. Results BLAST (basic local alignment search tool) analysis confirmed the accuracy of the morphological identification of all specimens as Ae. aegypti, with 100% similarity to GenBank sequences. Calculated variance and haplotype diversity were 0.502 and 0.00157, respectively. Among the 604 examined nucleotide sequences, only a single site was non-synonymous. Total nucleotide diversity and average pairwise nucleotides were determined as 0.00083 and 0.502, respectively. Fu and Li's D test values were not statistically significant. Strobeck’s S statistic value was 0.487, and Tajima’s D value was 1.53395; both were not statistically significant (P > 0.10). Conclusions Phylogenetic analysis revealed two distinct clades with minimal nucleotide differences and low haplotype diversity, suggesting the recent establishment of Ae. Aegypti in the southern region of Iran. The phylogenetic analysis also indicated an association between Ae. aegypti populations and mosquitoes from Saudi Arabia and Pakistan. Graphical Abstract